Über die Dipterenfauna des Stallbiotops (Untersuchungen über die Insektenfauna von Räumen: 10. Beitrag). - Kühlhorn, Friedrich jun. (Contributions to Entomology = Beiträge zur Entomologie, 1964)
The composition of the Dipterous fauna of stables is extensively determined by milieu conditions and capacity of development existing in the surroundings. Up to now 330 species of Diptera were found in stables and studied as to their time of appearance in the room and relations to it. Some of the species may be of any hygienic, parasitological or economic importance. A great number of other species also frequently found instables, where contacts to men and domestic animals are possible, have not yet been studied in this way. The above survey refers to such species too.